Direct Ink Writing of 3D Zn Structures as High‐Capacity Anodes for Rechargeable Alkaline Batteries. Issue 4 (15th December 2022) - Zhu, Cheng; Schorr, Noah B.; Qi, Zhen; Wygant, Bryan R.; Turney, Damon E.; Yadav, Gautam G.; Worsley, Marcus A.; Duoss, Eric B.; Banerjee, Sanjoy; Spoerke, Erik D.; van Buuren, Anthony; Lambert, Timothy N.
Abstract : The relationship between structure and performance in alkaline Zn batteries is undeniable, where anode utilization, dendrite formation, shape change, and passivation issues are all addressable through anode morphology. While tailoring 3D hosts can improve the electrode performance, these practices are inherently limited by scaffolds that increase the mass or volume. Herein, a direct write strategy for producing template‐free metallic 3D Zn electrode architectures is discussed. Concentrated inks are customized to build designs with low electrical resistivity (5 × 10 −4  Ω cm), submillimeter sizes (200 μm filaments), and high mechanical stability (Young's modulus of 0.1–0.5 GPa at relative densities of 0.28–0.46). A printed Zn lattice anode versus NiOOH cathode with an alkaline polymer gel electrolyte is then demonstrated. This Zn||NiOOH cell operates for over 650 cycles at high rates of 25 mA cm −2 with an average areal capacity of 11.89 mAh cm −2, a cumulative capacity of 7.8 Ah cm −2, and a volumetric capacity of 23.78 mAh cm −3 . A thicker Zn anode achieves an ultrahigh areal capacity of 85.45 mAh cm −2 and a volumetric capacity of 81.45 mAh cm −3 without significant microstructural changes after 50 cycles. Abstract : Zn colloidal inks are customized for direct writing of 3D Zn architectures with excellent physiochemical and mechanical properties. 3D Zn lattices are used to assemble quasisolid‐state Zn||NiOOH alkaline batteries, showing high areal capacity at high rates. Their long life cycles also enable the highest cumulative capacity compared to others, indicating excellent potential of printed Zn anodes for practical use.